Lithium secondary battery

By using low cobalt content of overlithiated manganese-based oxides and silicon-based negative electrode active materials in lithium secondary batteries, the shortcomings in fast charging performance, life characteristics and energy density of lithium secondary batteries are solved, and more efficient battery performance and lower production costs are achieved.

CN119812437APending Publication Date: 2025-04-11LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510008940.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-20
Filing Date
2022-07-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing lithium secondary batteries have shortcomings in fast charging performance, life characteristics and energy density, especially in terms of difficulty in maintaining stability at high voltages, resulting in structural collapse, transition metal dissolution and gas generation.

Method used

Using a low cobalt content of manganese-based oxide and silicon-based negative electrode active material, the oxygen-oxidation reduction reaction is reduced by controlling the Co content in the positive electrode active material to less than 10 mol % to suppress gas generation and positive electrode deterioration, and the irreversible capacity of the negative electrode is reduced by compensation of excess lithium.

Benefits of technology

The excellent fast charging performance, extended life characteristics and improved energy density of lithium secondary batteries are achieved, which reduces production costs and reduces the unevenness of reaction with the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812437A_ABST
    Figure CN119812437A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte, in which the positive electrode includes a positive electrode active material layer including a positive electrode active material including an over-lithiated manganese-based oxide represented by the following Formula 1, and the negative electrode includes a negative electrode active material layer including a silicon-based negative electrode active material and a carbon-based negative electrode active material, in which the content of the silicon-based negative electrode active material is 1 wt% to 30 wt% and the content of the carbon-based negative electrode active material is 70 wt% to 99 wt% with respect to the total weight of the negative electrode active material, [Formula 1] LiaNibCocMndMeO2 in Formula 1, satisfies 1lt; a, 0 < = b < = 0.5, 0 < = c < = 0.1, 0.5 < = dlt; 1.0 and 0 < = e < = 0.2, and M is at least one selected from the group consisting of Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of PCT international application PCT / KR2022 / 010679, with an application date of July 21, 2022. The original application is an invention patent application. The application number entering the Chinese national phase is 202280014192.4, and the name is "Lithium Secondary Battery". Technical Field

[0002] This application claims the benefit of Korean Patent Application No. 10-2021-0095985 filed on July 21, 2021, and No. 10-2022-0089894 filed on July 20, 2022, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to a lithium secondary battery, and more particularly, to a lithium secondary battery exhibiting excellent rapid charging performance, life characteristics and energy density. Background Art

[0004] Recently, with the growing interest in energy storage technology and the expansion of its application in mobile phones, cameras, laptop computers, and electric vehicles, efforts in research and development of electrochemical devices have been increasingly enriched.

[0005] Among these electrochemical devices, there has been an interest in developing rechargeable secondary batteries, and in particular, lithium secondary batteries developed in the early 1990s have attracted much attention due to their high operating voltage and significantly higher energy density.

[0006] Lithium secondary batteries are generally prepared by the following method. An electrode assembly is formed by providing a separator between a positive electrode and a negative electrode, the positive electrode comprising a positive electrode active material formed of a lithium-containing transition metal oxide, the negative electrode comprising a negative electrode active material capable of storing lithium ions, the electrode assembly is inserted into a battery case, a non-aqueous electrolyte as a medium for transporting lithium ions is injected, and then the battery case is sealed. The non-aqueous electrolyte is generally composed of a lithium salt and an organic solvent capable of dissolving the lithium salt.

[0007] Recently, the growing demand for secondary batteries with high energy density (such as batteries for electric vehicles) has brought about the active development of high-voltage secondary batteries driven at high voltage. In addition, research is being conducted to apply silicon-based negative electrode active materials with excellent capacity to obtain higher capacity.

[0008] Lithium secondary batteries for vehicles developed so far mainly use lithium nickel-based oxides as positive electrode active materials. When lithium nickel-based oxides are applied, problems such as structural collapse of the positive electrode active material at high voltage, dissolution of transition metals, gas generation, etc. are caused. In addition, when silicon-based negative electrode active materials are applied, sacrificial positive electrode materials are used to compensate for the high irreversible capacity of the silicon-based negative electrode active materials. In this case, the amount of positive electrode active material contained in the positive electrode is reduced, thereby reducing the battery capacity.

[0009] At the same time, there is a growing demand for lithium secondary batteries that exhibit excellent fast charging performance to shorten charging time, which has become the biggest stumbling block to the commercialization of electric vehicles. However, the fast-charging batteries developed so far cannot provide satisfactory performance in terms of lifespan or energy density.

[0010] Therefore, there is still a need to develop a lithium secondary battery that exhibits excellent rapid charging performance and minimizes degradation of lifespan and energy density. Summary of the invention

[0011] Technical issues

[0012] One aspect of the present invention provides a lithium secondary battery that exhibits excellent fast charging performance, lifespan characteristics, and energy density by applying an over-lithiated manganese-based oxide having a low cobalt content and a silicon-based negative electrode active material.

[0013] Technical Solution

[0014] According to one aspect of the present invention, a lithium secondary battery is provided, which includes a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode includes a positive electrode active material layer having a positive electrode active material, the positive electrode active material includes a perlithiated manganese-based oxide represented by the following formula 1, and the negative electrode includes a negative electrode active material layer having a silicon-based negative electrode active material.

[0015] [Formula 1]

[0016] Li a Ni b Co c Mn d M e O2

[0017] In Formula 1 above, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d ≤ 1.0, and 0 ≤ e ≤ 0.2 are satisfied, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr. Preferably, in Formula 1 above, 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.5 ≤ d ≤ 0.80, and 0 ≤ e ≤ 0.1 can be satisfied.

[0018] Meanwhile, the over-lithiated manganese-based oxide can be a mixture of a Li2MnO3 phase having a rock-salt structure and a LiM'O2 phase having a layered structure, and can be represented, for example, by Formula 2 below.

[0019] [Formula 2]

[0020] X Li2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M w O2

[0021] In Formula 2 above,

[0022] M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, and 0.1 ≤ X ≤ 0.5, 0.4 ≤ y < 1, 0 ≤ z ≤ 0.1, and 0 ≤ w ≤ 0.2 are satisfied.

[0023] Preferably, the D 50 of the positive electrode active material can be 2 μm to 10 μm, and the BET specific surface area can be 3 m 2 / g to 8 m 2 / g.

[0024] The energy density of the lithium secondary battery is 500 Wh / L or more, and it takes 20 minutes or less to quickly charge to 80% SOC.

[0025] Beneficial Effects

[0026] The present invention uses an over-lithiated manganese-based oxide (in which a Li2MnO3 phase having a rock-salt structure and a LiMO2 phase having a layered structure (where M is Ni, Co, Mn) are mixed) as the positive electrode active material, and uses a silicon-based negative electrode active material as the negative electrode active material. Therefore, the excess lithium generated by the Li2MnO3 phase during the activation process can compensate for the irreversible capacity of the silicon-based negative electrode active material. Therefore, in the lithium secondary battery of the present invention, the use of a sacrificial positive electrode material for negative electrode compensation or prelithiation can be minimized, thereby maximizing the positive electrode capacity.

[0027] In addition, the present invention uses a perlithiated manganese-based oxide with a low Co content of less than 10 mol% as a positive electrode active material to reduce the use of expensive Co, thereby reducing production costs, reducing oxygen-redox reactions to inhibit gas generation and positive electrode degradation, and reducing the heterogeneity of reactions with the negative electrode, and thus a secondary battery exhibiting excellent life characteristics, fast charging performance and energy density can be obtained.

[0028] In addition, compared with lithium nickel cobalt manganese oxide, over-lithiated nickel manganese cobalt oxide can be stably driven even at a relatively high voltage. Therefore, when a positive electrode active material containing over-lithiated manganese-based oxide is used together with a silicon-based negative electrode active material, a high energy density can be achieved by increasing the driving voltage.

[0029] Furthermore, the lithium secondary battery of the present invention includes a silicon-based negative electrode active material having excellent capacity and rate characteristics as a negative electrode active material, and thus exhibits excellent energy density and rapid charging performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the charge / discharge curve of a half-cell made using a cathode using Li 1.143 [Ni 0.33 Mn 0.67 ] 0.857 O2;

[0031] Figure 2 is an image showing that when single-walled carbon nanotubes are used as a conductive material, a conductive path is formed on the surface of a negative electrode active material;

[0032] Figure 3 is an image showing that when multi-walled carbon nanotubes are used as a conductive material, a conductive path is formed on the surface of a negative electrode active material. DETAILED DESCRIPTION

[0033] It will be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It will be further understood that based on the principle that the inventor can appropriately define the meaning of words or terms to best explain the present invention, the words or terms should be interpreted as having a meaning consistent with its meaning in the context of the relevant technology and the technical concept of the present invention.

[0034] In the present invention, the term "primary particle" means a particle unit having no observable grain boundary when observed in a field of view of 5000 to 20000 times using a scanning electron microscope. The term "average particle size of primary particles" means the arithmetic mean value calculated after measuring the particle size of primary particles observed in a scanning electron microscope image.

[0035] In the present invention, the term "secondary particle" refers to a particle formed by aggregation of a plurality of primary particles.

[0036] In the present invention, the term "average particle diameter D 50 " represents the particle diameter corresponding to 50% of the volume cumulative particle size distribution of the positive electrode active material powder. The average particle diameter D 50 can be measured by using a laser diffraction method. For example, when measuring "average particle diameter D 50 ", the positive electrode active material powder is dispersed in a dispersion medium, and the dispersion medium is introduced into a commercial laser diffraction particle size measuring instrument (such as Microtrac MT 3000), and irradiated with ultrasonic waves having a frequency of about 28 kHz and a power of 60 W to obtain a volume cumulative particle size distribution diagram, and then the particle diameter at 50% volume cumulative can be calculated.

[0037] Hereinafter, the present invention will be described in more detail.

[0038] The inventors of the present invention have found through intensive research that by using a hyperlithiated manganese-based oxide having a Co content of 10 mol% or less as a positive electrode active material and using a silicon-based negative electrode active material as a negative electrode active material, a lithium secondary battery exhibiting improved fast charging performance and minimizing deterioration of life characteristics and energy density can be obtained, and the present invention has been completed.

[0039] Specifically, the lithium secondary battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte. Among them, the positive electrode includes a positive electrode active material layer having a positive electrode active material, and the positive electrode active material contains a hyperlithiated manganese-based oxide represented by the following formula 1. The negative electrode includes a negative electrode active material layer having a silicon-based negative electrode active material.

[0040] [Formula 1]

[0041] Li a Ni b Co c Mn d M e O2

[0042] In the above formula 1, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d ≤ 1.0, and 0 ≤ e ≤ 0.2 are satisfied, and M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr. Preferably, in the above formula 1, 1.1 ≤ a ≤ 1.5, 0.1 ≤ b ≤ 0.4, 0 ≤ c ≤ 0.05, 0.5 ≤ d ≤ 0.80, and 0 ≤ e ≤ 0.1 can be satisfied.

[0043] Hereinafter, each component of the lithium secondary battery of the present invention will be described in detail.

[0044] positive electrode

[0045] The positive electrode of the present invention includes a perlithiated manganese-based oxide represented by Formula 1 as a positive electrode active material. Specifically, the positive electrode of the present invention may include a positive electrode collector and a positive electrode active material layer formed on at least one surface of the positive electrode collector, and the positive electrode active material layer may include a positive electrode active material containing a perlithiated manganese-based oxide represented by Formula 1.

[0046] [Formula 1]

[0047] Li a Ni b Co c Mn d M e O2

[0048] In the above Formula 1, M may be at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0049] Meanwhile, a is the molar ratio of Li in the over-lithiated manganese-based oxide, and may satisfy 1≤a≤1.2, 1.1≤a≤1.5, or 1.1≤a≤1.3. When a is within the above range, the irreversible capacity of the Si-based negative electrode active material may be fully compensated, and high capacity characteristics may be achieved.

[0050] The above b is a molar ratio of Ni in the over-lithiated manganese-based oxide, and may satisfy 0≤b≤0.5, 0.1≤b≤0.4, or 0.2≤b≤0.4.

[0051] The above c is the molar ratio of Co in the over-lithiated manganese-based oxide, and may satisfy 0≤c≤0.1, 0≤c≤0.08, or 0≤c≤0.05. When c is greater than 0.1, it may be difficult to achieve high capacity, and gas generation and greater degradation of the positive electrode active material may occur, resulting in a shortened lifespan.

[0052] The above d is the molar ratio of Mn in the over-lithiated manganese-based oxide, and may satisfy 0.5≤d<1.0, 0.50≤d≤0.80 or 0.50≤d≤0.70. When d is less than 0.5, the proportion of the rock salt phase becomes too small, making the negative electrode irreversible compensation and capacity improvement insignificant.

[0053] The above e is a molar ratio of the doping element M in the over-lithiated manganese-based oxide, and may satisfy 0≤e≤0.2, 0≤e≤0.1, or 0≤e≤0.05. When the content of the doping element is too high, the capacity of the active material may be adversely affected.

[0054] Over-lithiated manganese-based oxides containing excess lithium have a structure in which a layered phase (LiM'O2) and a rock salt phase (Li2MnO3) are mixed, and during the initial activation process, the rock salt phase is activated to produce excess lithium ions, thereby compensating for the irreversible capacity of the negative electrode, and thus a balance with the silicon-based negative electrode can be achieved without the need for a separate compensation material (such as a sacrificial positive electrode material) or a pre-lithiation compensation process (such as pre-lithiation). However, during the activation process of the rock salt phase, an oxygen-redox reaction occurs, a large amount of gas is generated, and greater degradation of the positive electrode is caused due to internal cracks in the active material and the collapse of the crystal structure, thereby shortening the life, and in particular, when the over-lithiated manganese-based oxide is applied to a secondary battery using a Si-based negative electrode active material as the negative electrode active material, the life is severely shortened.

[0055] The present inventors have found through intensive studies that when the Co content in the over-lithiated manganese-based oxide is controlled to be 10 mol % or less, the reduction in life can be suppressed even in combination with a Si-based negative electrode active material, and have completed the present invention.

[0056] It is not clear why the lifespan increases when a perlithiated manganese-based oxide having a Co content of 10 mol% or less is applied, but when Co in the layered structure is oxidized, the oxygen-redox reaction tends to increase at high voltage, and therefore, it is speculated that when the reaction is minimized, gas generation and degradation of the positive electrode active material are reduced.

[0057] At the same time, Si-based negative electrode active materials react faster with lithium than typical carbon-based negative electrode active materials, so lithium secondary batteries using a mixture of Si-based negative electrode active materials and carbon-based negative electrode active materials have been proposed to improve fast charging performance. However, in the case of a negative electrode using Si-based negative electrode active materials and carbon-based negative electrode active materials together, due to the difference in reaction rate between the carbon-based negative electrode active material and the Si-based negative electrode active material, an uneven reaction occurs in the negative electrode, and when the reaction unevenness increases, the life of the secondary battery deteriorates rapidly. At the same time, since Co is an element that promotes the formation of a layered crystal structure, when the Co content in the positive electrode active material increases, the layered crystal structure is well formed, and therefore, the lithium mobility is improved, making the reaction rate difference between the negative electrode active materials during charge / discharge more obvious. Therefore, in the present invention, when the Co content in the over-lithiated manganese-based oxide is controlled to be less than 10 mol%, the increase in reaction unevenness in the negative electrode can be suppressed to improve the life characteristics of the secondary battery.

[0058] Meanwhile, in the over-lithiated manganese-based oxide represented by the above formula 1, the molar ratio of Li to all metal elements other than Li (Li / Me) may be 1.2 to 1.5, 1.25 to 1.5, or 1.25 to 1.4. When the Li / Me ratio satisfies the above range, the rate characteristics and capacity characteristics are excellent. When the Li / Me ratio is too high, the conductivity decreases and the rock salt phase (Li2MnO3) increases, resulting in faster degradation, while when the Li / Me ratio is too low, the energy density improvement is not obvious.

[0059] Meanwhile, the composition of the over-lithiated manganese-based oxide may be represented by Formula 2 below.

[0060] [Formula 2]

[0061] X Li2MnO3·(1-X)Li[Ni 1-y-z-w Mn y Co z M w ]O2

[0062] In the above formula 2, M may be at least one selected from the group consisting of metal ions Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0063] The above X represents the ratio of the Li2MnO3 phase in the over-lithiated manganese-based oxide, and may satisfy 0.2≤X≤0.5, 0.25≤X≤0.5, or 0.25≤X≤0.4. When the ratio of the Li2MnO3 phase in the over-lithiated manganese-based oxide satisfies the above range, the irreversible capacity of the Si-based negative electrode active material may be fully compensated, and high capacity characteristics may be obtained.

[0064] The above y is a molar ratio of Mn in the LiM'O2 layered phase, and may satisfy 0.4≤y<1, 0.4≤y≤0.8, or 0.4≤y≤0.7.

[0065] The above z is the molar ratio of Co in the LiM'O2 layered phase and may satisfy 0≤z≤0.1, 0≤z≤0.08 or 0≤z≤0.05. When z is greater than 0.1, gas generation and greater degradation of the positive electrode active material may occur, resulting in a shortened lifespan.

[0066] The above w is a molar ratio of the doping element M in the LiM'O2 layered phase, and may satisfy 0≤w≤0.2, 0≤w≤0.1, or 0≤w≤0.05.

[0067] Meanwhile, the positive active material of the present invention may further include a coating on the surface of the over-lithiated manganese-based oxide as required. When the positive active material includes the coating, the coating prevents contact between the over-lithiated manganese-based oxide and the electrolyte to reduce the side reaction of the electrolyte, thereby improving the life characteristics.

[0068] The coating may contain a coating element M 1 , and coating element M 1 It may be, for example, at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr and Zr, preferably Al, Co, Nb, W and a combination thereof, more preferably Al, Co and a combination thereof. Two or more coating elements M may be included 1 , for example, may contain Al and Co.

[0069] The coating element may be present in the coating in the form of an oxide, i.e. 1 Oz(1≤z≤4).

[0070] The coating can be formed by methods such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD) or atomic layer deposition (ALD). Among them, the coating is preferably formed by an atomic layer deposition method, which provides the formation of a wide coating area.

[0071] The coating formation area may be 10% to 100%, preferably 30% to 100%, more preferably 50% to 100% of the total surface area of ​​the overlithiated manganese-based particles. When the coating formation area satisfies the above range, the improvement of life characteristics is significant.

[0072] Meanwhile, the positive electrode active material of the present invention may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the average particle size D of the secondary particles is 50 It can be 2 μm to 10 μm, preferably 2 μm to 8 μm, and more preferably 4 μm to 8 μm. 50 When the above range is satisfied, a satisfactory electrode density can be obtained, and degradation of capacity and rate characteristics can be minimized.

[0073] In addition, the BET specific surface area of ​​the positive electrode active material can be 1 m 2 / g to 10m 2 / g, 3m 2 / g to 8m 2 / g, or 4m 2 / g to 6m 2When the BET specific surface area of ​​the positive electrode active material is too low, it may be difficult to obtain sufficient capacity due to insufficient reaction area with the electrolyte, while when the specific surface area is too high, moisture absorption is fast and side reactions with the electrolyte are accelerated, making it difficult to ensure life characteristics.

[0074] In addition, the positive electrode of the present invention preferably has an initial irreversible capacity of about 5% to 70%, 5% to 50%, or 5% to 30%. The initial irreversible capacity of the positive electrode is a value measured relative to 0.1C as a percentage of the discharge capacity when charging / discharging in the voltage range of 2.5V to 4.4V to the charge capacity when activated at a high voltage of 4.6V or more.

[0075] When the initial irreversible capacity of the positive electrode satisfies the above range, the irreversible capacity of the silicon-based negative electrode active material can be fully compensated without using a separate compensation material (eg, a sacrificial positive electrode material).

[0076] As in the present invention, when the over-lithiated manganese-based oxide represented by the above formula 1 is used as the positive electrode active material, the use of high-priced Co can be reduced to reduce the manufacturing cost and obtain a high electrode density. The following Table 1 is a table comparing the prices of commercially available over-lithiated manganese-based oxide positive electrode active materials with the prices of NCMA-based positive electrode active materials.

[0077]

Table 1

[0078]

[0079] As shown in Table 1 above, the price of the positive electrode active material 2 with a low Co content is lower than that of NCMA or the positive electrode active material 1, and therefore, when the overlithiated manganese-based oxide with a low Co content is applied, the production cost of the lithium secondary battery can be reduced.

[0080] Meanwhile, the over-lithiated manganese-based oxide may be prepared by mixing a transition metal precursor with a lithium raw material and then firing the mixture.

[0081] The lithium raw material can be, for example, lithium-containing carbonates (e.g., lithium carbonate), hydrates (e.g., lithium hydroxide hydrate (LiOH·H2O), etc.), hydroxides (e.g., lithium hydroxide, etc.), nitrates (e.g., lithium nitrate (LiNO3)), chlorides (e.g., lithium chloride (LiCl)), etc., and they can be used alone or as a mixture of two or more thereof.

[0082] Meanwhile, the transition metal precursor may be in the form of a hydroxide, an oxide or a carbonate. When a carbonate-type precursor is used, it is more preferred that a positive electrode active material having a relatively high specific surface area can be obtained.

[0083] The transition metal precursor can be prepared by a coprecipitation process. For example, the transition metal precursor can be prepared by dissolving each transition metal-containing raw material in a solvent into a metal solution, then mixing the metal solution, an ammonium cation complexing agent and an alkaline compound, and then performing a coprecipitation reaction to prepare. In addition, an oxidant or oxygen can also be added in the coprecipitation reaction as required.

[0084] In this case, the raw material containing the transition metal may be acetate, carbonate, nitrate, sulfate, halide, sulfide, etc. of each transition metal. Specifically, the raw material containing the transition metal may be NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halide, etc.

[0085] The ammonium cation complexing agent may be at least one selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4 and (NH4)2CO3.

[0086] The alkaline compound may be at least one selected from the group consisting of NaOH, Na2CO3, KOH and Ca(OH)2. The form of the precursor may vary depending on the type of alkaline compound used. For example, when NaOH is used as the alkaline compound, a hydroxide-type precursor may be obtained, and when Na2CO3 is used as the alkaline compound, a carbonate-type precursor may be obtained. In addition, when the alkaline compound is used together with an oxidant, an oxide-type precursor may be obtained.

[0087] Meanwhile, the transition metal precursor and the lithium raw material may be mixed in an amount such that a molar ratio of the total transition metal (Ni+Co+Mn):Li is 1:1.05 to 1:2, preferably 1:1.1 to 1:1.8, more preferably 1:1.25 to 1:1.8.

[0088] Meanwhile, firing may be performed at 600° C. to 1000° C. or 700° C. to 950° C., and firing may be performed for 5 to 30 hours or 5 to 20 hours. In addition, the firing atmosphere may be an air atmosphere or an oxygen atmosphere, for example, an atmosphere containing 20% ​​to 100% by volume of oxygen.

[0089] Meanwhile, the positive electrode active material layer may further include a conductive material and a binder in addition to the positive electrode active material.

[0090] The conductive material may be, for example, spherical or flaky graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotube, and multi-walled carbon nanotube; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more of them may be used. The content of the conductive material may be 0.1% to 20% by weight, 1% to 20% by weight, or 1% to 10% by weight relative to the total weight of the positive electrode active material layer.

[0091] In addition, the binder can be, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one of them or a mixture of two or more thereof can be used. Relative to the total weight of the positive electrode active material layer, the content of the binder can be 1 wt % to 20 wt %, 2 wt % to 20 wt %, or 2 wt % to 10 wt %.

[0092] Meanwhile, the electrode density of the positive electrode of the present invention may be about 2.5 g / cc to 3.8 g / cc, 2.5 g / cc to 3.5 g / cc, or 3.0 g / cc to 3.3 g / cc. When the electrode density of the positive electrode satisfies the above range, high energy density can be obtained.

[0093] As described above, in the lithium secondary battery of the present invention using the overlithiated manganese-based oxide represented by Formula 1 as the positive electrode active material, the cell is stably driven even when the charge termination voltage is set as high as 4.3V to 4.5V during battery driving, so high capacity can be obtained.

[0094] Figure 1 The charge / discharge curves of a half-cell fabricated using a cathode using an overlithiated manganese-based oxide as the cathode active material are shown. Figure 1 As shown, it can be seen that the positive electrode using the over-lithiated manganese-based oxide as the positive electrode active material produces excess lithium at a high voltage above 4.6V and is stably driven at a voltage above 4.3V.

[0095] negative electrode

[0096] The negative electrode of the present invention contains a silicon-based negative electrode active material as the negative electrode active material. Specifically, the negative electrode of the present invention may include a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the negative electrode current collector, and the negative electrode active material layer may contain a silicon-based negative electrode active material as the negative electrode active material.

[0097] The silicon-based negative electrode active material has a higher theoretical capacity than the carbon-based negative electrode active material and reacts faster with lithium. Therefore, when the silicon-based negative electrode active material is included in the negative electrode, the energy density and fast charging performance are improved. However, the silicon-based negative electrode active material has a large irreversible capacity and a large volume expansion during charge / discharge, and thus exhibits poor life characteristics. In particular, when the silicon-based negative electrode active material is used in combination with a lithiated manganese-based oxide that undergoes an oxygen-redox reaction, the life characteristics are further deteriorated. In addition, when the silicon-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, due to the difference in the reaction rate between the silicon-based negative electrode active material and the carbon-based negative electrode active material, non-uniformity is caused in the negative electrode, resulting in the deterioration of the negative electrode. However, as in the present invention, when a lithiated manganese-based oxide with a controlled Co content is used in combination with the silicon-based negative electrode active material, the oxygen-redox reaction is reduced, thereby minimizing the deterioration of the life characteristics and obtaining excellent energy density and fast charging performance.

[0098] The silicon-based negative electrode active material may be, for example, Si, SiOw (0 < w ≤ 2), Si-C composite material, Si-M a alloy (M a is at least one selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), or a combination thereof.

[0099] Meanwhile, if necessary, the silicon-based negative electrode active material may be doped with M b metal, and in this case, the M b metal may be a Group 1 alkali metal element and / or a Group 2 alkaline earth metal element, such as Li, Mg, etc. Specifically, the silicon-based negative electrode active material may be Si, SiOw (0 < w ≤ 2), Si-C composite material, etc. doped with M b metal. In the case of the silicon-based negative electrode active material doped with metal, the active material may have a reduced capacity due to the doping element, but has high efficiency and thus obtains a high energy density.

[0100] In addition, as required, the silicon-based negative electrode active material may also include a carbon coating on the particle surface. In this case, the carbon coating amount may be 20 wt % or less, preferably 0.1 wt % to 20 wt % relative to the total weight of the silicon-based negative electrode active material. When the carbon coating is applied, the conductivity of the silicon surface may be increased, thereby improving the uniformity of the SEI layer, and improving the initial efficiency and life characteristics.

[0101] The carbon coating may be formed by a method such as dry coating, wet coating, chemical vapor deposition (CVD), physical vapor deposition (PVD), or atomic layer deposition (ALD).

[0102] Meanwhile, the capacity of the silicon-based negative electrode active material is preferably 1000mAh / g to 4000mAh / g, preferably 1000mAh / g to 3800mAh / g, and more preferably 1200mAh / g to 3800mAh / g. When a silicon-based negative electrode active material satisfying the above capacity range is used, high capacity characteristics can be obtained.

[0103] In addition, the silicon-based negative electrode active material may have an initial efficiency of 60% to 95%, 70% to 95%, preferably 75% to 95%. The initial efficiency of the silicon-based negative electrode active material represents the percentage of discharge capacity to charge capacity, which is measured by manufacturing a half-cell having a negative electrode and a lithium counter electrode using 100% silicon-based negative electrode active material as a negative electrode active material, and then charging / discharging at a 0.1C rate between 0.01V and 1.5V. When the initial efficiency of the silicon-based negative electrode active material satisfies the above range, the lithium provided from the positive electrode can be used reversibly, and excellent fast charging performance can be obtained.

[0104] In addition, the particle size D of the silicon-based negative electrode active material 50 It can be 3 μm to 8 μm, preferably 4 μm to 7 μm, and D min To D max It can be 0.01 μm to 30 μm, preferably 0.01 μm to 20 μm, and more preferably 0.5 μm to 15 μm. When the particle size of the silicon-based negative electrode active material meets the above range, sufficient electrode density can be ensured by the silicon-based negative electrode active material alone or the silicon-based negative electrode active material mixed with the carbon-based negative electrode active material.

[0105] In addition, as required, the negative electrode may also contain a carbon-based negative electrode active material as the negative electrode active material. The carbon-based negative electrode active material may be, for example, artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, hard carbon, etc., but is not limited thereto.

[0106] Meanwhile, the content of the silicon-based negative electrode active material may be 1 wt % to 100 wt %, 1 wt % to 50 wt %, 1 wt % to 30 wt %, 1 wt % to 15 wt %, 10 wt % to 70 wt %, or 10 wt % to 50 wt %, relative to the total weight of the negative electrode active material.

[0107] Relative to the total weight of the negative electrode active material, the content of the carbon-based negative electrode active material can be 0 wt % to 99 wt %, 50 wt % to 99 wt %, 70 wt % to 99 wt %, 85 wt % to 99 wt %, 30 wt % to 90 wt %, or 50 wt % to 90 wt %.

[0108] Meanwhile, in the lithium secondary battery of the present invention, it is preferred that different N / P ratios, ie, the ratio of the negative electrode discharge capacity to the positive electrode discharge capacity, be configured according to the type of the negative electrode active material used.

[0109] For example, when a mixture of SiO and a carbon-based negative electrode active material is used as the negative electrode active material, the N / P ratio may be 100% to 150%, preferably 100% to 140%, and more preferably 100% to 120%. When the negative electrode discharge capacity exceeds the above range relative to the positive electrode discharge capacity, the balance between the positive electrode and the negative electrode cannot be ensured, and the life characteristics may be deteriorated or lithium precipitation may occur.

[0110] In addition, when 100% Si is used as the negative electrode active material, the N / P ratio may be 150% to 300%, preferably 160% to 300%, and more preferably 180% to 300%. When the negative electrode discharge capacity exceeds the above range relative to the positive electrode discharge capacity, the balance between the positive electrode and the negative electrode cannot be ensured, and the life characteristics may be deteriorated or lithium precipitation may occur.

[0111] Meanwhile, the negative electrode active material layer may further include a conductive material and a binder as needed.

[0112] The conductive material may be, for example, spherical or flaky graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, single-walled carbon nanotube, and multi-walled carbon nanotube; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more of them may be used. The content of the conductive material may be 0.1% to 30% by weight, 0.1% to 20% by weight, or 0.1% to 10% by weight relative to the total weight of the negative electrode active material layer.

[0113] Preferably, single-walled carbon nanotubes may be used as the conductive material. When carbon nanotubes are used as the conductive material, a wide conductive path is formed to increase durability and reduce resistance, thereby obtaining excellent life characteristics.

[0114] Figure 2 is an image showing a conductive path formed on the surface of a negative electrode active material when single-walled carbon nanotubes are used as a conductive material; Figure 3 is an image showing a conductive path formed on the surface of a negative electrode active material when multi-walled carbon nanotubes are used as a conductive material.

[0115] like Figure 2 and Figure 3 As shown, when single-walled carbon nanotubes are used as a conductive material, a conductive path is uniformly formed on the surface of the negative electrode active material, thereby improving the cycle characteristics.

[0116] In addition, the binder can be, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one of them or a mixture of two or more thereof can be used. Relative to the total weight of the negative electrode active material layer, the content of the binder can be 1 wt % to 20 wt %, 2 wt % to 20 wt %, or 2 wt % to 10 wt %.

[0117] Meanwhile, the negative electrode may have a multilayer structure in which the negative electrode active material layer consists of a single layer or two or more layers. For example, the negative electrode may include a first negative electrode active material layer formed on the negative electrode current collector and a second negative electrode active material layer formed on the first negative electrode active material.

[0118] When the negative electrode active material layer has a multilayer structure consisting of two or more layers, each layer may have a different kind and / or content of negative electrode active material, binder and / or conductive material.

[0119] For example, in the first negative electrode active material layer (lower layer), the content of carbon-based negative electrode active material in the whole negative electrode active material may be higher than that in the second negative electrode active material layer (upper layer), in the second negative electrode active material layer, the content of silicon-based negative electrode active material in the whole negative electrode active material may be higher than that in the first negative electrode active material layer, or the content of conductive material in the second negative electrode active material layer (upper layer) may be higher than that in the first negative electrode active material layer (upper layer).

[0120] As described above, by forming a negative electrode active material layer having a multilayer structure and changing the composition of each layer, the performance characteristics of the battery can be improved. For example, when the content of the conductive material or the silicon-based negative electrode active material in the upper layer is higher than that in the lower layer, the fast charging performance can be improved.

[0121] Meanwhile, the porosity of the negative electrode active material layer may be 20% to 70% or 20% to 50%. When the porosity of the negative electrode active material layer is too small, electrolyte impregnation may be reduced, thereby deteriorating lithium mobility, and when the porosity is too large, energy density may be reduced.

[0122] Diaphragm

[0123] In the lithium secondary battery of the present invention, the separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions. Any separator can be used without particular limitation, as long as it is commonly used as a separator in a lithium secondary battery. In particular, it is preferred that the electrolyte has a high moisture retention capacity and a separator with low resistance to the movement of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by a polyolefin polymer (such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof can be used. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed by a glass fiber with a high melting point, a polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be selectively used.

[0124] Electrolytes

[0125] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in the manufacture of a lithium secondary battery, but is not limited thereto.

[0126] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0127] Any organic solvent can be used without particular limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following solvents can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone.

[0128] Any compound can be used as the lithium salt without particular limitation as long as it can provide lithium ions for use in a lithium secondary battery. Specifically, the anion of the lithium salt can be selected from the group consisting of F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - At least one of the group consisting of, and LiPF6, LiN(FSO2)2, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2 can be used as the lithium salt. The lithium salt can be used in a concentration range of 0.1M to 5.0M.

[0129] In addition, additives may be included in the electrolyte for the purpose of increasing battery life, suppressing capacity reduction, preventing gas generation, etc. As additives, various additives used in the art may be used, such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinylethylene carbonate (VEC), ethylene sulfate (ESa), lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate) (LiDFBP), lithium tetrafluorooxalatophosphate (LiTFOP), lithium methyl sulfate (LiMS), lithium ethyl sulfate (LiES), propane sultone (PS), propylene sultone (PRS), succinonitrile (SN), adiponitrile (AND), 1,3,6-hexanetrionitrile (HTCN), 1,4-dicyano-2-butene (DCB), fluorobenzene (FB), ethyl di(prop-2-yn-1-yl) phosphate (EDP), 5-methyl-5-propargyloxycarbonyl-1,3-dioxetan-2-one (MPOD), a compound represented by the following formula A (e.g., cyanoethyl polyvinyl alcohol, PVA-CN), a compound represented by formula B (e.g., heptafluorobutylcyanoethyl polyvinyl alcohol, PF-PVA-CN), a compound represented by formula C (e.g., propargyl 1H-imidazole-1-carboxylate, PAC), and / or a compound represented by formula D (e.g., aryl imidazole, such as C6H8N2), and the like.

[0130] [Formula A]

[0131]

[0132] In the above formula A, n and m are each independently an integer of 1 to 100.

[0133] [Formula B]

[0134]

[0135] [Formula C]

[0136]

[0137] In the above formula C, R 16 is a linear or nonlinear alkylene group having 1 to 3 carbon atoms, R 17 To R 19 are each independently at least one selected from the group consisting of hydrogen, an alkyl group having 1 to 3 carbon atoms, and -CN, and D is CH or N.

[0138] [Formula D]

[0139]

[0140] In the above formula D, R1, R2, R3 and R4 may each independently include: hydrogen; or an alkyl group having 1 to 5 carbon atoms, a cyano group (CN), an allyl group, a propargyl group, an amine group, a phosphate group, an ether group, a phenyl group, a cyclohexyl group, a silyl group, an isocyanate group (-NCO), a fluoro group (-F).

[0141] Preferably, a compound used as an oxygen scavenger can be used as an additive. As a compound used as an oxygen scavenger, tris(trimethylsilyl)phosphite (TMSPi), tris(trimethyl)phosphite (TMPi), tris(2,2,2-trifluoroethyl)phosphite (TTFP) and other phosphite-based structures (see formula E), tris(trimethylsilyl)phosphate (TMSPa), trimethylsilylpolyphosphate (PPSE), tris(pentafluorophenyl)borane (TPFPB), coumarin-3-nitrile (CMCN), 7-ethynylbenzene Coumarin (ECM), 3-acetylcoumarin (AcCM), 3-[(trimethylsilyl)oxy]-2H-1-benzopyran-2-one (TMSOCM), 3-(trimethylsilyl)coumarin (TMSCM), 3-(2-propyn-1-yloxy)-2H-1-benzopyran-2-one (POCM), 2-propyn-1-yl-2-oxo-2H-1-benzopyran-3-carboxylate (OBCM), and compounds containing coumarin structure (see formula F), etc.

[0142] [Formula E]

[0143]

[0144] [Formula F]

[0145]

[0146] In formulas E and F, R1 to R6 may each independently include cyano (nitrile), fluorine (F), ether (COC), carboxyl (OC=O), trimethylsilyl (-TMS), isocyanate (-NCO) and / or isothiocyanate (-NCS) functional groups, which are substituted or unsubstituted alkenyl groups having 2 to 20 carbon atoms and substituted or unsubstituted alkynyl groups having 2 to 20 carbon atoms.

[0147] The lithium secondary battery of the present invention configured as described above can compensate for the irreversible capacity of the silicon-based negative electrode active material by performing the activation process at a high voltage of 4.6 V or more, using lithium generated during the activation process of the Li2MnO3 phase.

[0148] The lithium secondary battery of the present invention configured as described above exhibits high energy density and excellent fast charging performance. Specifically, the lithium secondary battery of the present invention has an energy density of 500Wh / L or more, preferably 500Wh / L to 1000Wh / L, and fast charging to 80% ΔSOC takes less than 20 minutes.

[0149] Example

[0150] Hereinafter, specific examples will be provided to illustrate the present invention in detail.

[0151] Example 1

[0152] The positive electrode active material, single-walled carbon nanotubes and PVDF binder were mixed in N-methylpyrrolidone at a weight ratio of 96.0:1.0:3 to prepare a positive electrode slurry. In this case, Li coated with Al (1500 ppm) was used. 1.143 [Ni 0.35 Mn 0.65 ] 0.857 O2 is used as the positive electrode active material.

[0153] The positive electrode slurry was applied to an aluminum current collector sheet, dried, and then roll-pressed to prepare a positive electrode.

[0154] A negative electrode active material, single-walled carbon nanotubes, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in water at a weight ratio of 96.2:0.8:2:1 to prepare a first negative electrode slurry.

[0155] In addition, the negative electrode active material, single-walled carbon nanotubes, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in water at a weight ratio of 93.8:1.2:4:1 to prepare a second negative electrode slurry.

[0156] Graphite having an initial efficiency of 94% and SiOx having an initial efficiency of 82% were mixed as negative electrode active materials in the first negative electrode slurry and the second negative electrode slurry in such a way that the weight ratio of graphite to SiOx (SiOx:C) was 5:95 and then used.

[0157] The first negative electrode slurry was applied to a copper current collector sheet and dried, and then the second negative electrode slurry was applied thereto, dried, and then roll-pressed to prepare a double-layer negative electrode.

[0158] At the same time, a positive electrode and a negative electrode were prepared, and the loading amount was controlled so that the ratio of the discharge capacity of the negative electrode to the discharge capacity of the positive electrode (N / P ratio) was 115%.

[0159] The separator was placed between the positive electrode and the negative electrode prepared above to prepare an electrode assembly, and the electrode assembly was inserted into a battery case. Thereafter, an electrolyte was injected, and an activation process was performed by charging to 4.6V at a constant current of 0.1C at 45°C and then discharging to 2.0V at a constant current of 0.1C to manufacture a lithium secondary battery.

[0160] Example 2

[0161] In addition to using Li coated with Al (1500 ppm) 1.143 [Ni 0.34 Co 0.02 Mn 0.64 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as a positive electrode active material.

[0162] Example 3

[0163] In addition to using Li without Al coating 1.143 [Ni 0.34 Co 0.02 Mn 0.64 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as a positive electrode active material.

[0164] Example 4

[0165] In addition to using Li coated with Al (1500 ppm) 1.130 [Ni 0.35 Mn 0.65 ] 0.870 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as a positive electrode active material.

[0166] Example 5

[0167] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn 0.67 ]0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1, except that O2 was used as a positive electrode active material and multi-walled carbon nanotubes were used instead of single-walled carbon nanotubes when preparing the first negative electrode slurry and the second negative electrode slurry.

[0168] Example 6

[0169] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn 0.67 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1, except that O2 was used as a positive electrode active material, and the second negative electrode slurry was applied to a copper current collector sheet, dried, and then roll-pressed to prepare a single-layer negative electrode.

[0170] Example 7

[0171] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn 0.67 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as the positive electrode active material and the loading amounts of the positive and negative electrodes were adjusted so that the ratio of the negative electrode discharge capacity to the positive electrode discharge capacity (N / P ratio) was 120%.

[0172] Example 8

[0173] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn 0.67 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857A lithium secondary battery was manufactured in the same manner as in Example 1, except that O2 was used as a positive electrode active material, and SiOx and graphite were mixed at a weight ratio of 10:90 (SiOx:C) as negative electrode active materials of the first negative electrode slurry and the second negative electrode slurry.

[0174] Example 9

[0175] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn 0.67 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as the positive electrode active material, SiC was used alone as the negative electrode active material of the first negative electrode slurry and the second negative electrode slurry, and the ratio of the negative electrode discharge capacity to the positive electrode discharge capacity (N / P ratio) was 250%.

[0176] Comparative Example 1

[0177] In addition to using Li coated with Al (1500 ppm) 1.143 [Ni 0.22 Co 0.12 Mn 0.66 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as a positive electrode active material.

[0178] Comparative Example 2

[0179] In addition to using LiNi coated with Al (1500ppm) 0.80 Co 0.10 Mn 0.10 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1 except that O2 was used as a positive electrode active material.

[0180] Comparative Example 3

[0181] Using Li coated with Al (1500 ppm) 1.143 [Ni 0.33 Mn0.67 ] 0.857 O2 replaces Li coated with Al (1500ppm) 1.143 [Ni 0.35 Mn 0.65 ] 0.857 A lithium secondary battery was manufactured in the same manner as in Example 1, except that O2 was used as the positive electrode active material, graphite was used alone as the negative electrode active material in the first negative electrode slurry and the second negative electrode slurry, and the ratio of the negative electrode discharge capacity to the positive electrode discharge capacity (N / P ratio) was 112%.

[0182]

Table 2

[0183]

[0184] Experimental Example 1:

[0185] The irreversible capacity of the positive electrode and the initial efficiency of the negative electrode prepared in the examples and comparative examples were measured as follows. The measurement results are shown in Table 3 below.

[0186] <Measurement of Irreversible Capacity of Positive Electrode>

[0187] A half-cell was prepared using each of the positive electrodes and lithium counter electrodes prepared in the examples and comparative examples. Then, the half-cell was charged to 4.65 V at 45° C. with a constant current of 0.1 C, and then discharged to 2.0 V with a constant current of 0.1 C to perform an activation process. Then, the charge capacity C1 during the activation process was measured.

[0188] Then, the half-cell after the activation process was completed was charged to 4.35 V with a constant current of 0.1 C at 25 ° C, and discharged to 2.5 V with a constant current of 0.1 C to measure the cycle discharge capacity D1. The percentage of the discharge capacity D1 relative to the charge capacity C1 during the activation process was calculated to measure the irreversible capacity of the positive electrode.

[0189] <Measurement of Initial Efficiency of Negative Electrode>

[0190] A half-cell was prepared using each negative electrode and lithium counter electrode prepared in the Examples and Comparative Examples. After applying a current to 0.005 V at a constant current of 0.1 C at 25° C., the half-cell was charged to 0.05 V at a constant potential of 0.005 V and discharged to 1.5 V at a constant current of 0.1 C, and then the percentage of the discharge capacity relative to the charge capacity was measured.

[0191]

Table 3

[0192]

[0193] Experimental Example 2: Number of cycles to reach 80% lifespan

[0194] The secondary batteries prepared in the examples and comparative examples were charged to 4.2 V at a constant current of 0.33 C and discharged to 2.5 V at a constant current of 0.33 C at 25° C. and discharged as one cycle to measure the number of times the discharge capacity reached 80% relative to the initial discharge capacity after one cycle. The measurement results are shown in Table 4 below.

[0195] Experimental Example 3: Fast Charging Performance

[0196] The secondary batteries prepared in the embodiments and comparative examples were charged by a step-by-step charging method, and the time (unit: minutes) required to charge to 80% SOC was measured. In this case, step-by-step charging is a method of sequentially charging by reducing the charging rate when a constant voltage (4.35V) is reached after charging at a constant charging rate (C-rate), and in the present invention, it is sequentially performed under the C-rate conditions of 3C→2.5C→2C→1.5C→1C→0.5C→0.1C. The measurement results are shown in Table 4 below.

[0197] Experimental Example 4: Energy density (unit: Wh / L)

[0198] The secondary batteries prepared in the examples and comparative examples were charged and discharged in a voltage range of 4.35V to 2.5V, and the energy density of the secondary batteries was measured. The energy density was calculated by multiplying the discharge capacity by the average voltage and then dividing by the unit volume of the secondary battery, and the average voltage was the value obtained by dividing the integral value of the capacity-voltage curve by the capacity. The measurement results are shown in Table 4 below.

[0199]

Table 4

[0200] Number of cycles to reach 80% life Fast charging (minutes) Energy density (Wh / L) Example 1 671 19.5 523 Example 2 648 19.2 528 Example 3 696 19.7 532 Example 4 676 19.5 525 Example 5 644 19.9 528 Example 6 685 20.0 530 Example 7 690 18.8 530 Example 8 652 18.5 524 Example 9 576 15.4 476 Comparative Example 1 601 22.3 513 Comparative Example 2 711 25 520 Comparative Example 3 530 31 503

[0201] As shown in Table 4 above, the lithium secondary batteries of Examples 1 to 8 (in which an overlithiated manganese-based oxide having a Co content of less than 10 mol% is used as a positive electrode active material, and a mixture of SiOx and graphite is used as a negative electrode active material) exhibit excellent fast charging performance of less than 20 minutes, excellent life characteristics with a capacity retention rate of more than 80% after more than 640 charges / recharges, and excellent energy density of more than 520Wh / L.

[0202] The lithium secondary battery of Example 9 using 100% SiC as the negative electrode active material exhibited slightly reduced capacity and lifespan, but exhibited fairly excellent rapid charging performance.

[0203] Meanwhile, the lithium secondary battery of Comparative Example 1 applying the overlithiated manganese-based oxide having a Co content of 10 mol % or more failed to satisfy the fast charging performance of less than 20 minutes and exhibited lower lifespan and energy density than the lithium secondary battery of the embodiment.

[0204] Compared with the lithium secondary battery of the embodiment, the lithium secondary battery of Comparative Example 2 (in which NCM 811 was used instead of the overlithiated manganese-based oxide as the positive electrode active material) exhibited excellent lifespan, but low rapid charging performance and energy density.

[0205] Compared with the lithium secondary battery of the embodiment, the lithium secondary battery of Comparative Example 3 (in which only graphite of a carbon-based negative electrode active material is applied as the negative electrode active material) exhibits lower fast charging performance, life and energy density, and in particular, exhibits significant deterioration in life and fast charging performance.

Claims

1. A lithium secondary battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode includes a positive electrode active material layer containing a positive electrode active material, the positive electrode active material contains a lithiated manganese-based oxide represented by Formula 1, and the negative electrode includes a negative electrode active material layer containing a silicon-based negative electrode active material and a carbon-based negative electrode active material, in, with respect to the total weight of the negative electrode active material, the content of the silicon-based negative electrode active material is 1 wt% to 30 wt%, and the content of the carbon-based negative electrode active material is 70 wt% to 99 wt%, [Formula 1] Li a Ni b Co c Mr d M e O2 In Formula 1 above, 1 < a, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.1, 0.5 ≤ d < 1.0, and 0 ≤ e ≤ 0.2 are satisfied, and M is at least one selected from the group consisting of Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

2. The lithium secondary battery according to claim 1, wherein In Formula 1, 0 < c ≤ 0.

08.

3. The lithium secondary battery according to claim 1, wherein The lithiated manganese-based oxide has a structure in which a layered phase and a rock salt phase are mixed.

4. The lithium secondary battery according to claim 1 or 3, wherein: The lithiated manganese-based oxide is represented by Formula 2: [Formula 2] X Li2MnO3·(1-X)Li[Ni 1-y-z-w Mr y Co z M w ]O2 In Formula 2 above, M is at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr, and 0.2 ≤ X ≤ 0.5, 0.4 ≤ y < 1, 0 ≤ z ≤ 0.1, and 0 ≤ w ≤ 0.2 are satisfied.

5. The lithium secondary battery according to claim 1, wherein The positive electrode active material D 50 2μm to 10μm.

6. The lithium secondary battery according to claim 1, wherein The BET specific surface area of ​​the positive electrode active material is 1 m 2 / g to 10m 2 / g.

7. The lithium secondary battery according to claim 1, wherein The initial irreversible capacity of the positive electrode is 5% to 70%.

8. The lithium secondary battery according to claim 1, wherein The electrode density of the positive electrode is 2.5 g / cc to 3.8 g / cc.

9. The lithium secondary battery according to claim 1, wherein: The initial efficiency of the silicon-based negative electrode active material is 60% to 95%.

10. The lithium secondary battery according to claim 1, wherein The negative electrode active material layer further contains a conductive material and a binder, and the conductive material includes single-walled carbon nanotubes.

11. The lithium secondary battery according to claim 1, wherein The silicon-based negative electrode active material D 50 3μm to 8μm.

12. The lithium secondary battery according to claim 1, wherein The porosity of the negative electrode active material layer is 20% to 70%.

13. The lithium secondary battery according to claim 1, wherein: The negative electrode has a multilayer structure including two or more negative electrode binder layers.

14. The lithium secondary battery according to claim 1, wherein: The negative electrode includes a negative electrode current collector, a first negative electrode binder layer provided on the negative electrode current collector, and a second negative electrode binder layer provided on the first negative electrode binder layer, and the second negative electrode binder layer has a higher content of the conductive material than the first negative electrode binder layer.

15. The lithium secondary battery according to claim 1, wherein: The energy density of the lithium secondary battery is 500 Wh / L or more, and it takes 20 minutes or less to quickly charge to 80% SOC.

Citation Information

Patent Citations

  • Systems and methods for a network-based video game application

    KR1020210095985A

  • Apparatus for laundary treatment

    KR1020220089894A